Is It Time for a Citizens' Bill of Educational Entitlement? - Wharton, Clifton R., Jr. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
A hypothetical outline of a federal bill of educational entitlement proposes: (1) every high school graduate who is a citizen of the United States would be eligible for a specific federal dollar entitlement per year up to a maximum of four years of full-time study within a 10-year period immediately following graduation. (2) After the initial 10-year period, the individual would acquire additional educational entitlement benefits for every year he or she paid federal income tax or met the requirement for federal negative income tax assistance. (3) A citizen's educational entitlement could be used at any accredited public or private postsecondary institution in the United States and its territorial possessions. (4) The federal entitlement would apply to all regardless of need. The rationale for the entitlement and this type of approach are discussed emphasizing the potential abuses of excessive educational consumerism and institutional aid. (Author/MJM)
ERIC Note: Paper presented at the National Conference on Higher Education sponsored by the American Association for Higher Education (30th, Chicago, Illinois, March 1975).
Educational level discussed: Higher Education.
Educational level discussed: Postsecondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Finance; Educational Innovation; Federal Aid; Federal Programs; Financial Policy; Financial Support; Higher Education; Postsecondary Education; Speeches; Student Costs; Tuition; Entitlement; Speeches/Meeting Papers